AEROFOTOGRAFIAS DE BAIXO CUSTO COMO INSTRUMENTO DE MONITORAMENTO AMBIENTAL - Izola, Dawson Tadeu; Picollo, Paulo [UNESP]; Catalano, Fernando Martini (Departamento de Engenharia Agrícola - UFCG, 1998)
At present pictures in aerial photographics are taken by aeroplanes with special cameras and spots taken by satellites with remote sensory equipment. The proposal of this work is to use a small rocket with a 2.000m range. The load of this rocket is a 35mm lens camera with a 40 pictures film. The camera separates at the highest point of the rocket trajectory and is retrieved at ground level after a parachute descent. During the camera fall an electronic circuit takes photos at controlled intervals, thereby creating the scale of the sequence of photographs.

Atualmente, utilizam-se fotos aéreas obtidas de aviões equipados com câmaras especiais e spots conseguidos através de satélites de sensoriamento remoto. A proposta deste trabalho é utilizar-se um foguete de pequeno porte com alcance de 2.000m cuja carga útil é uma câmara fotográfica de 35mm com capacidade de 40 fotos. A câmara é abandonada no ponto mais alto da trajetória e retorna ao solo amparada por um pára-quedas, no período de queda, quando um circuito eletrônico dispara a câmara com intervalos controlados estabelecendo, assim, a escala da seqüência de fotos.
LOW COST AEROFOTOGRAPHY WITH ENVIROMENTAL MONITORING EQUIPMENT
Keywords: aerial photograph; rocket; basic stamp; foto aérea; foguete; basic stamp